Surgical Strategy in Uterine Leiomyomas: The Impact of Patient Characteristics and Fertility Desire on Technique Selection and Perioperative Outcomes - Cihan Bademkıran; Vehbi Yavuz Tokgöz; Ahmet Başar Tekin (Women’s Health and Multidisciplinary Research, 2026)
Background and Aim: Uterine leiomyomas are among the most common benign gynecologic conditions requiring surgical intervention. The selection of a surgical strategy is influenced by multiple patient-specific factors, particularly fertility desire; however, data evaluating how these factors shape surgical decision-making and perioperative outcomes remain limited. This study aimed to evaluate the relationships among patient characteristics, fertility desire, surgical technique selection, and perioperative outcomes in patients undergoing surgery for uterine leiomyomas. Materials and Methods: This retrospective observational study included 266 patients who underwent surgical treatment for uterine leiomyomas between January 2007 and December 2012. Patients were classified according to the surgical approach as hysterectomy, myomectomy, or hysteroscopic myomectomy. Demographic, obstetric, and clinical characteristics were recorded, and perioperative outcomes, including intraoperative blood loss, postoperative hemoglobin levels, length of hospital stay, transfusion requirements, and complications, were analyzed. Fertility desire was inferred from patient age, parity, and documented reproductive preferences in the medical records. Statistical comparisons were performed using appropriate parametric and nonparametric tests. Results: The surgical approach was significantly associated with patient age and reproductive characteristics. Patients undergoing hysterectomy were older and had higher gravidity and parity, whereas uterus-preserving approaches were more commonly performed in younger patients with a less extensive reproductive history (p